Karakteristik Fisik dan Organoleptik Sirup Buah Galoba dengan Penambahan Sukrosa - Tetelepta, Gilian (Jurnal Agrosilvopasture-Tech, 2025)
Galoba (Hornstedtia alliacea) is a local fruit commodity from Maluku characterized by abundant juice and a distinctive sweet–sour flavor, making it suitable for syrup production. This study aimed to determine the optimal sucrose concentration for producing high-quality galoba syrup based on physical and sensory properties. A completely randomized design with one factor—sucrose concentration—was applied, with three replications. The results indicated that the 70% sucrose treatment yielded the best outcomes, with a pH of 3.42 and total soluble solids (TSS) of 60.33 °Brix. Sensory evaluation showed favorable scores for color (3.15), taste (3.55), aroma (3.35), texture (2.55), and overall acceptance (3.60). In terms of hedonic quality, the syrup was characterized by a brownish-yellow color (2.85), sweet taste (3.40), distinctive galoba aroma (2.95), and thick texture (2.60). These findings suggest that a 70% sucrose concentration produces galoba syrup with desirable physicochemical and sensory attributes.